2011
DOI: 10.3727/096504011x13021877989711
|View full text |Cite
|
Sign up to set email alerts
|

Tea Polyphenols Induce Apoptosis Through Mitochondrial Pathway and by Inhibiting Nuclear Factor-κB and Akt Activation in Human Cervical Cancer Cells

Abstract: Phytochemicals present in tea, particularly polyphenols, have anticancer properties against several cancer types. However, studies elucidating the role and the mechanism(s) of action of tea polyphenols in cervical cancer are sparse. In this study, we investigated the mechanism of antiproliferative and apoptotic actions exerted by tea polyphenols on human papilloma virus-18-positive HeLa cervical cancer cells. Treatment of green tea polyphenol (-)-epigallocatechin gallate (EGCG) and black tea polyphenol theafla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 10 publications
(16 reference statements)
3
51
0
Order By: Relevance
“…43 Excessive generation of ROS and a decline in ΔΨm has been documented in cancer cells treated with tea polyphenols. 4,6,7 Notably, in our study, these results were also observed at a low concentration of TF/EGCG-NPs (1/20th, 1/10th and 1/5th of the respective bulk IC 50 dose), again confirming the marked dose advantage achieved when TF/EGCG is delivered using a NP formulation.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…43 Excessive generation of ROS and a decline in ΔΨm has been documented in cancer cells treated with tea polyphenols. 4,6,7 Notably, in our study, these results were also observed at a low concentration of TF/EGCG-NPs (1/20th, 1/10th and 1/5th of the respective bulk IC 50 dose), again confirming the marked dose advantage achieved when TF/EGCG is delivered using a NP formulation.…”
supporting
confidence: 74%
“…35 We have already documented the potential of tea polyphenols in inhibition of NF-κB activity. 6,7 In our present study, we noted the significant effect of a low concentration of TF/EGCG-NPs on chemosensitivity to CDDP (IC 20 dose) via inhibition of NF-κB and its corresponding gene. It was found that low doses of TF/EGCG-loaded NPs (1/20th, 1/10th, and 1/5th of the respective bulk IC 50 dose) suppressed NF-κB activation more efficiently in combination with CDDP than did the bulk TF/EGCG (IC 50 dose).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Researches have shown that disregulation of NF-κB transcription machinery is one of the factors thought to be common early events in malignant tumor progression (Meng et al, 2012). Thus, it is becoming increasingly clear that compounds that block NF-κB activation could be highly useful for the treatment of cancers (Singh et al, 2011). Bcl-2 and Bcl-X L are members of the Bcl-2 family regulated by NF-κB.…”
Section: Discussionmentioning
confidence: 99%